Transient weak gravity in scalar-tensor theories - Wittner, Manuel; Laverda, Giorgio; Piattella, Oliver F.; Amendola, Luca (Journal of cosmology and astroparticle physics, 2020)
Sub-horizon perturbations in scalar-tensor theories have been shown to grow generically faster than in uncoupled models due to a positive, additive Yukawa force. In such cases, the amount of clustering becomes larger than in the standard cosmological model, exacerbating the observed tension in the σ8 parameter. Here we show instead that in some simple cases of conformally coupled dark energy one can obtain a transient regime of negative Yukawa force, without introducing ghosts or other instabilities.
Gesehen am 05.10.2020